Teens who hurt : clinical interventions to break the cycle of adolescent violence - Hardy, Kenneth V. (Guilford Press, 2005)
Offering a fresh perspective on treatment, this book presents an overarching framework and many specific strategies for working with violent youth and their families. The authors shed light on the complex interplay of individual, family, community, and societal forces that lead some adolescents to hurt others or themselves. Effective ways to address each of these factors in clinical and school settings are discussed and illustrated with evocative case material. The book provides essential guidance on connecting with aggressive teens and their parents and managing difficult situations that are.